The Poverty Impacts of Climate Change : A Review of the Evidence - Skoufias, Emmanuel; Rabassa, Mariano; Olivieri, Sergio (2012)
Climate change is believed to represent a serious challenge to poverty reduction efforts around the globe. This paper conducts an up-to-date review of three main strands of the literature analyzing the poverty impacts of climate change : (i) economy-wide growth models incorporating climate change impacts to work out consistent scenarios for how climate change might affect the path of poverty over the next decades; (ii) studies focusing on the poverty impacts of climate change in the agricultural sector; and (iii) studies exploring how past climate variability impacts poverty. The analysis finds that the majority of the estimates of the poverty impacts tend to ignore the effect of aggregate economic growth on poverty and household welfare. The empirical evidence available to date suggests that climate change will slow the pace of global poverty reduction, but the expected poverty impact will be relatively modest and far from reversing the major decline in poverty that is expected to occur over the next 40 years as a result of continued economic growth. The studies focusing on the sector-specific channels of impacts of climate change suggest that the estimated impacts of climate change on agricultural yields are generally a poor predictor of the poverty impacts of climate change at the national level due to heterogeneity in the ability of households to adapt. It also appears that the impacts of climate change are generally regressive, that is, they fall more heavily on the poor than the rich.